Directors' tenure and their independence: capital market perspective - Malik @ Malek, Mazrah; Saidin, Saidatunur Fauzi; Abdul Hamid, Mohamad Ali (Institute for Strategic and Sustainable Accounting Development, Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia, 2016)
The independence of non-executive directors has long been a concern. The independent directors are not only required to be independent from management but also free from any other relationships which can interfere with their objectivity. Recently, the concern has been focused on long tenure of independent directors. Regulators seem to believe that long tenure may impair independence, hence attempts to limit the tenure have been recommended, even though it has not been made mandatory. However, theories concerning long tenure are contradictory and empirical evidences are weak. Earlier studies are based on theory-driven approach, which only examines the association between directors’ tenure and proxies of financial reporting quality. This study on the other hand, proposes a different approach based on earnings response coefficient model which not only examines investors’ perceptions but also their reactions. This is based on the widely accepted independence model where independence should not only be in the form of fact but also appearance. The interaction between directors’ tenure and earnings performance is hypothesized to have a significant negative relationship with the cumulative abnormal return. Low perceived earnings quality in financial accounts from long tenure by investors is expected to result in lower coefficient of earnings. This study will provide additional literature and knowledge on the effect of independent directors’ tenure. It can assist regulators in revising the requirement for directors’ tenure.